Incidence of cutaneous melanoma and Merkel cell carcinoma in patients with primary cutaneous B-cell lymphomas: A population study of the SEER registry - Banner, Lauren; Joffe, Daniel; Lee, Emily; Porcu, Pierluigi; Nikbakht, Neda (Frontiers in Medicine, 2023)
Introduction The increased incidence of cutaneous melanoma (CM) and Merkel cell carcinoma (MCC) in patients with hematologic malignancies (HM) is well established. While the risk of CM has been assessed in some subtypes of HM including cutaneous T-cell lymphoma, the incidence in patients with primary cutaneous B-cell lymphoma (PCBCL) has not been interrogated. Methods Here we evaluated the standardized incidence ratio (SIR) of CM and MCC in 5,179 PCBCL patients compared to approximately 1.5 billion individuals in the general population using the Surveillance, Epidemiology and End Results (SEER) database. Among patients with PCBCL, we identified subgroups that were at increased risk for CM or MCC as a second primary cancer. Results We found 36 cases of CM in the PCBCL cohort (SIR, 1.35; 95% CI, 0.94–1.86), among which SIR was significantly elevated for non-Hispanic White patients compared to the general population (SIR, 1.48; 95% CI, 1.03–2.06). Males had a significantly increased risk of developing CM after a diagnosis of PCBCL (SIR, 1.60; 95% CI, 1.10–2.26). We found that males in the age group of 50–59 were at increased risk for CM development (SIR, 3.02; 95% CI, 1.11–6.58). Males were at increased risk of CM 1–5 years after PCBCL diagnosis (SIR, 2.06; 95% CI, 1.18–3.34). Patients were at greater risk of developing MCC within 1 year of diagnosis of PCBCL (SIR, 23.60; 95% CI, 2.86–85.27), particularly in patients who were over the age of 80 (SIR, 46.50; 95% CI, 5.63–167.96). Males aged 60–69 with PCBCL, subtype marginal zone, were also at increased risk for MCC (SIR, 42.71; 95% CI, 1.08–237.99). Conclusion There is an increased incidence of CM in White, middle-aged males within 5 years of diagnosis of PCBCL and an increased risk of MCC in elderly patients within 1 year of PCBCL diagnosis. These data suggest that certain subgroups of patients with PCBCL may require more rigid surveillance for CM and MCC.